STRATEGIC IMPLEMENTATION OF MARKETING MANAGEMENT AT TMRN CAFE - Safitri, Lucky (Dinasti International Journal of Digital Business Management, 2020)
TMRN Restoran Cafe is one of the businesses engaged in culinary services and products that has the motto of having a variety of foods and delicious flavors and accompanied design that creates comfort. The purpose of this article is to conduct an analysis of external and internal factors which are the strengths and weaknesses of TMRN Resto and Cafe using qualitative descriptive data analysis methods. This article obtains results from TMRN Cafe which require a work structure in order to have each employee's work desk as well as company standard SOPs that are made in a directed and clear manner, in addition to developing or increasing marketing through radio and events or bazaars, making cards a member for TMRN Cafe loyal customers. The strategy that is best implemented and managed will help in the business development process that is carried out.